Designing a physical activity parenting course: Parental views on recruitment, content and delivery - Jago Russell; Steeds Joanna K; Bentley Georgina F; Sebire Simon J; Lucas Patricia J; Fox Kenneth R; Stewart-Brown Sarah; Turner Katrina M (BMC, 2012)
Abstract Background Many children do not engage in sufficient levels of physical activity (PA) and spend too much time screen-viewing (SV). High levels of SV (e.g. watching TV, playing video games and surfing the internet) and low levels of PA have been associated with adverse health outcomes. Parenting courses may hold promise as an intervention medium to change children's PA and SV. The current study was formative work conducted to design a new parenting programme to increase children's PA and reduce their SV. Specifically, we focussed on interest in a course, desired content and delivery style, barriers and facilitators to participation and opinions on control group provision. Methods In-depth telephone interviews were conducted with thirty two parents (29 female) of 6-8 year olds. Data were analysed thematically. An anonymous online survey was also completed by 750 parents of 6-8 year old children and descriptive statistics calculated. Results Interview participants were interested in a parenting course because they wanted general parenting advice and ideas to help their children be physically active. Parents indicated that they would benefit from knowing how to quantify their child's PA and SV levels. Parents wanted practical ideas of alternatives to SV. Most parents would be unable to attend unless childcare was provided. Schools were perceived to be a trusted source of information about parenting courses and the optimal recruitment location. In terms of delivery style, the majority of parents stated they would prefer a group-based approach that provided opportunities for peer learning and support with professional input. Survey participants reported the timing of classes and the provision of childcare were essential factors that would affect participation. In terms of designing an intervention, the most preferred control group option was the opportunity to attend the same course at a later date. Conclusions Parents are interested in PA/SV parenting courses but the provision of child care is essential for attendance. Recruitment is likely to be facilitated via trusted sources. Parents want practical advice on how to overcome barriers and suggest advice is provided in a mutually supportive group experience with expert input.